2003
DOI: 10.4049/jimmunol.170.12.6266
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-Triggered Lipoxin A4 and B4 Analogs Block Extracellular Signal-Regulated Kinase-Dependent TNF-α Secretion from Human T Cells

Abstract: Lipoxins (LX) and their aspirin-triggered 15-epimer endogenous isoforms are endogenous anti-inflammatory and pro-resolution eicosanoids. In this study, we examined the impact of LX and aspirin-triggered LXA4-stable analogs (ATLa) on human T cell functions. 15-epi-16-(p-fluoro)phenoxy-LXA4 (ATLa1) blocked the secretion of TNF-α from human PBMC after stimulation by anti-CD3 Abs, with the IC50 value of ≈0.05 nM. A similar action was also exerted by the native aspirin-triggered 15-epi-LXA4, a new 15-epi-16-(p-trif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 170 publications
(125 citation statements)
references
References 46 publications
7
117
1
Order By: Relevance
“…p38-MAPK provides a proapoptotic/"death" signal for neutrophils that can be overridden by a survival signal generated by p42/p44-ERK (49). Treatment of human T cells with 10 nM ATLa for 6 h blocks activation of ERK and release of TNF-␣ upon subsequent stimulation of these cells with an anti-CD3 Ab (50). These data are consistent with ATLa blocking the proinflammatory effects of a variety of immune cells by targeting MAPKs.…”
Section: Discussionsupporting
confidence: 74%
“…p38-MAPK provides a proapoptotic/"death" signal for neutrophils that can be overridden by a survival signal generated by p42/p44-ERK (49). Treatment of human T cells with 10 nM ATLa for 6 h blocks activation of ERK and release of TNF-␣ upon subsequent stimulation of these cells with an anti-CD3 Ab (50). These data are consistent with ATLa blocking the proinflammatory effects of a variety of immune cells by targeting MAPKs.…”
Section: Discussionsupporting
confidence: 74%
“…ANXA-1 has been shown to promote the detachment of neutrophils adhered to the inflamed endothelium, hence reducing the number of cells that migrate into the subendothelial space (51). In addition, the latter mediators have also been shown to prevent the production of TNF-␣ in various models of inflammation (52,53). As neutrophils and TNF-␣ cooperate to mediate reperfusion-induced injury and lethality, the above-mentioned effects could account for the protective effects of LXA 4 and ANXA-1 in mice.…”
Section: Analogue Atl-1 or The Anxa-1-derived Peptide Ac2-26 Does Notmentioning
confidence: 99%
“…T Cell Incubations-Cytokines (TNF␣ and IFN␥) produced by human T cells were determined as described in Ariel et al (28). Briefly, human peripheral blood T cells were incubated with increasing concentrations of PD1 or vehicle (0.05% EtOH) for 6 h at 37°C and then in 48-well plates coated with anti-CD3 ϩ anti-CD28 (2 g/ml each) or anti-CD3 alone and cultured for 41 h. The supernatants were collected from the wells and evaluated for TNF␣ and IFN␥ content by a standard enzyme-linked immunosorbent assay.…”
Section: Methodsmentioning
confidence: 99%
“…2) suggested that lymphocytes are one of the main targets of PD1. Next we examined the impact of PD1 on the secretion of cytokines by human peripheral blood T cells because cytokine deprivation per se participates in the resolution of inflammation and is regulated by other lipid mediators of resolution, such as lipoxins (28). Antibodies against CD3 and CD28 were used to mimic the stimulation by antigen-presenting cells that leads to the secretion of TNF␣ and IFN␥ by T cells.…”
Section: Pd1 Generation By Human T H 2-skewed Pbmc Is Dependent On Exmentioning
confidence: 99%